Information Technology and Market Orientation on the Competitiveness and Performance of a Kuningan's Tourism Activity - Gunawan, Wely Hadi; Wachyuni, Wachyuni (Jurnal Minds: Manajemen Ide dan Inspirasi, 2020)
Kuningan local tourism possesses a promising future. However, some investigations cite a decrease in visitors over time, revealing underlying problems in the organization. Critical inquiries may arise from the interaction of information technology and market orientation to increase competitiveness and, finally, tourist attractions' performance. Thus, this study investigates the local tourism activity of Panembongan Hill in Kuningan, Banten, Indonesia. One hundred thirty visitors agree to participate in the study, and the coded responses are analyzed using structural equation modeling. The results reveal that Information Technology does not relate to competitiveness and tourism business performance; market orientation increases competitiveness and business performance. Finally, the competitiveness of tourism activities propels business performance considerably.